Changes in microstructures and hydrogen permeability of Nb30Hf35Co35 eutectic alloy membranes by annealing. (21st January 2016) - Yan, Erhu; Sun, Lixian; Xu, Fen; Zou, Yongjin; Chu, Hailiang; Zhang, Huanzhi; Sun, Yixin
Abstract: Changes in microstructures and hydrogen permeability by long-time annealing (168 h) at 1073, 1173 and 1173 K for eutectic Nb30 Hf35 Co35 alloy are investigated. After annealing at 1073 K and 1173 K for 168 h, the fully lamellar eutectic microstructure in as-cast state has disappeared and turned to a duplex microstructure. Correspondingly, the hydrogen permeability at 673 K, decreases from 3.3 × 10 −8 to (0.82–1.5) × 10 −8 mol H2 m −1 s −1 Pa −0.5 after annealing. The annealed (a-) sample at 1273 K for 168 h is brittle and susceptible to hydrogen embrittlement that results from the appearance of the additional Hf2 Co phase. The hydrogen solubility coefficient ( K ) for each a- samples at 673 K is almost the same as that for the as-cast sample, while the hydrogen diffusion coefficient ( D ) for the a- samples are (1/4–1/2) times than that for the as-cast one. It is thus concluded that the lower permeability by annealing for eutectic Nb30 Hf35 Co35 is mainly attributed to the significant reduction of hydrogen diffusivity after annealing. Highlights: Drastic change of microstructure is found for the as-cast alloy after annealing. The hydrogen permeability of the as-cast alloy reduces significantly after annealing. The lower Φ is mainly attributed to the significant reduction of D after annealing. Annealing can't enhance the hydrogen permeability of Nb30 Hf35 Co35 alloy.